2009
DOI: 10.1016/j.mod.2009.06.842
|View full text |Cite
|
Sign up to set email alerts
|

20-P009 Lipid phosphate phosphatases controlling germ and heart cell biology

Abstract: During development, the pancreatic endocrine cells are specified within the epithelium. They will subsequently delaminate and migrate out of the epithelium in order to form the islets.Neurogenin3 (Ngn3) is a bHLH transcription factor that is responsible for differentiation of all endocrine cell types, but whether or not it has a role in their migration is still an open question. By using the chicken embryo model organism, we found that differentiation and migration programs are two different processes that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To test whether they also regulate heart cell matching, we imaged the CB filopodia activity (Figure 2A) by driving Moesin (Moe)::GFP (Dutta et al, 2002) expression in all CBs using Hand-Gal4 (Han, 2006). As reported previously (Haack et al, 2014;Swope et al, 2014), CBs filopodia are highly dynamic, protruding and retracting repeatedly (Video S3 Left). At a cell center separation of $15-20 mm, we observed that contralateral CBs initiate physical contacts through filopodia (Figure 2A).…”
Section: Filopodia Show Differential Binding Affinity In Distinct Cb Subtypesmentioning
confidence: 88%
See 1 more Smart Citation
“…To test whether they also regulate heart cell matching, we imaged the CB filopodia activity (Figure 2A) by driving Moesin (Moe)::GFP (Dutta et al, 2002) expression in all CBs using Hand-Gal4 (Han, 2006). As reported previously (Haack et al, 2014;Swope et al, 2014), CBs filopodia are highly dynamic, protruding and retracting repeatedly (Video S3 Left). At a cell center separation of $15-20 mm, we observed that contralateral CBs initiate physical contacts through filopodia (Figure 2A).…”
Section: Filopodia Show Differential Binding Affinity In Distinct Cb Subtypesmentioning
confidence: 88%
“…As the molecular mechanisms of CB filopodia formation and activity are still unknown (Haack et al, 2014), we perturbed filopodia activity in CBs by expressing a dominant-negative allele of Cdc42 (Cdc42 N17 ) (Luo et al, 1994) using Hand-Gal4. Cdc42 is a small GTPase that regulates polarity establishment, cell migration and filopodia activity (Hall, 1998;Mattila and Lappalainen, 2008), and in contrast to Rac and Rho, it is essential for heart morphogenesis and lumen formation (Swope et al, 2014;Vogler et al, 2014).…”
Section: Filopodia Show Differential Binding Affinity In Distinct Cb Subtypesmentioning
confidence: 99%